Chronostratigraphy of Jerzmanowician. New data from Koziarnia Cave, Poland. (August 2021) - Kot, Małgorzata; Krajcarz, Maciej T.; Hoyo, Magdalena Moskal-del; Gryczewska, Natalia; Wojenka, Michał; Pyżewicz, Katarzyna; Sinet-Mathiot, Virginie; Diakowski, Marcin; Fedorowicz, Stanisław; Gąsiorowski, Michał; Marciszak, Adrian; Lipecki, Grzegorz; et al.
Highlights: Jerzmanowician occupation in Koziarnia Cave (layer D) can be dated to 39-36 ky calBP. Long chronology of the LRJ technocomplex exceeding the CI event can be suggested. layers K/K' show one of the oldest Gravettian occupations N to the Carpathians. Radiocarbon dates demonstrate alternate cave occupation by humans and cave bears. Abstract: Lincombian-Ranisian-Jerzmanowician (LRJ) industries are extremely scarce in Central Europe. Therefore, each LRJ site is of great importance. One of them is Koziarnia Cave in Poland situated eastwards relative to other LRJ sites. Our investigations of this cave provided new chronostratigraphic data for the LRJ industries. A detail debitage analysis recognised the ventral thinning chips and enabled identification of the LRJ assemblage-containing stratum. Besides the LRJ assemblage, strata with traces of Late Middle Palaeolithic and Early Gravettian occupation were found at the site. The radiocarbon dates of Koziarnia samples show that the archaeological settlement represents one of the oldest Gravettian stays north to the Carpathians. Moreover, these dates demonstrate that humans and cave bears had alternately occupied the cave. Additionally, the radiocarbon dates indicate relatively young chronology of the Jerzmanowician occupation in Koziarnia Cave (ca. 39-36 ky calBP). The results suggest the long chronology of the LRJ technocomplex, exceeding the Campanian Ignimbrite event.